Pengaruh Komunikasi Dan Budaya Organisasi Terhadap Kinerja Karyawan - Tri Mulyani Kartini (Direktorat Penelitian dan Pengabdian Masyarakat (DPPM) Universitas Pelita Bangsa, 2020)
This research was conducted to examine the influence of communication and organizational culture on employee performance at PT. XY. The population in this study were all employees of PT XY, totaling 262 employees. This study uses a quantitative approach, the data for this study were obtained through a questionnaire that had been filled in by PT XY employees, namely 50 respondents. The data analysis method used is the SPSS method of multiple linear regression. This study tested three variables, namely: communication (X1), organizational culture (X2) as the independent variable and employee performance (Y) as the dependent variable. The results showed that communication and organizational culture had a significant effect on employee performance at PT XY.